Experiences of family medicine specialist in providing health care for LGBT patients: A qualitative study in East Coast Peninsular Malaysia - Mohd Amin, Siti Noorfadhilah; Muhamad, Rosediani; Mohd Zulkifli, Maryam; Draman, Samsul (2022)
Recent years have witnessed a growing health concern over lesbian, gay, bisexual, and transgender (LGBT) community in Malaysia, particularly for human immunodeficiency virus infection (HIV) and sexually transmitted infection (STI). LGBT patients continue to report discrimination in healthcare setting despite the effort of primary healthcare practitioners offering community friendly services. This qualitative study aimed to provide understanding of the current issue and to explore the challenges that family medicine specialists (FMS) face when dealing with LGBT patients.30 FMSs working in East Coast Peninsular Malaysia were interviewed through a phenomenological framework using semi-structured in-depth interviews. The interviews were recorded, transcribed verbatim, and managed in an analytic computer software NVivo 12. The data were then analysed thematically. Their experiences revealed three overlapping themes; (i) LGBT phenomenon as deviation from social norms and vulnerable members of society, (ii) obstacles in providing culturally competent care, and (iii) barriers incorporating spiritual needs for holistic care. Lack of formal training, the existence of stigma, challenging patients' personalities, and unfavourable clinic setting are the four main barriers cited by the FMS. This study shed light on the sensitive issue of LGBT in Malaysia and the current situation related to the challenges faced by FMS when dealing with LGBT patients. In order to successfully overcome those challenges, proper training of healthcare personnel and a collaborative effort with other relevant authorities is essential.